2010
DOI: 10.5171/2010.985461
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Moderating Factors in Mobile Coupon Adoption: An Extended TAM Perspective

Abstract: This research represents a theoretical extension of the extended Technology Acceptance Model (TAM) to study the consumer adoption of mobile coupons. We developed a model to test the relationship between theoretical constructs spanning technological and cognitive influence processes and their impact on Behavioural Intention. This study aims to integrate price consciousness and value consciousness into the promotional effectiveness framework. The results of the study indicate that perceived usefulness and percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 16 publications
(29 reference statements)
2
18
0
5
Order By: Relevance
“…This can have an indirect impact on consumers' attitudes toward and intention to use mobile coupons. This finding supports the argument of Jayasingh and Eze (2010), that CP will be positively related to attitudes toward using mobile coupons.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This can have an indirect impact on consumers' attitudes toward and intention to use mobile coupons. This finding supports the argument of Jayasingh and Eze (2010), that CP will be positively related to attitudes toward using mobile coupons.…”
Section: Discussionsupporting
confidence: 90%
“…The technology acceptance model (TAM; Davis, 1989) has been commonly adopted in previous studies of mobile coupon redemption (e.g., Dickinger & Kleijnen, 2008;Jayasingh & Eze, 2009, 2010. Lichtenstein et al (1990) found that psychological factors, such as coupon proneness and value consciousness, have a positive impact on coupon redemption.…”
mentioning
confidence: 98%
“…A number of models/theories designed to facilitate the understanding of factors impacting the acceptance and use of technologies have been documented. Some of the well known technology acceptance models and theories include: Theory of Reasoned Action (TRA); Motivational Model (MM); Theory of Planned Behaviour (TPB); Decomposed Theory of Planned Behaviour (DTPB); Technology Acceptance Model (TAM); Technology Acceptance Model (TAM2); Combined TAM and TPB (C-TAM-TPB); Model of PC Utilization (MPCU); Social Cognitive Theory (SCT); Innovation Diffusion Theory (IDT) and; the Unified Theory of Acceptance and Use of Technology (UTAUT) (Venkatesh et al, 2003;Kripanont, 2007;Wu, Tao and Yang, 2007;Ghobakhloo, Zulkifli and Aziz, 2010;Jayasingh and Eze, 2010). Due to the existence of several competing technology acceptance theories and models as noted above, researchers analyse and compare them in order to identify the most promising ones in respect of the ability to predict and explain individual behaviour towards the acceptance and usage of technology.…”
Section: Introductionmentioning
confidence: 99%
“…Jayasingh and Eze (2010), in their study of mobile coupon adoption, note that attitudes towards coupon usage are influenced by perceptions of how useful the coupon or deal is; perceived ease of use (i.e., redemption); the individual's proneness to enjoy coupon shopping; and perceptions of the credibility of the coupon distributor. Furthermore, actual intention to use coupons is impacted not only by an individual's attitude towards coupons, but also by their level of personal innovativeness regarding technology use, the social influence of their peers, and the extent to which coupon purchase and redemption is compatible with their overall lifestyle (Jayasingh & Eze, 2010).…”
Section: Influence Of Coupon Adoption On Buyer Behaviormentioning
confidence: 98%